(untitled) (Al-Academy, 2024)
Art in television was known for the diversity of the work of the elements of the media’s language, as in the case of cinema, these elements that the director relies on by employing their work as expressive and aesthetic tools, enabling the work maker to produce content that carries several meanings with it, or to give the displayed image connotations that refer the viewer to Understanding is greater than the borders of the picture frame itself. The employment of language elements is based on intellectual foundations in terms of content, and aesthetic in terms of form, through a series of directive processing that falls on the director, as he draws and builds the features of traditional dramatic work in general, And black comedy works in drama in particular, as black comedy has its goals politically, socially and economically, and it also has its own style that it deliberately raises and addresses those topics that are forbidden in the monotheistic religions, or those that are considered taboos in some societies, armed with the principle of paradox between Laughter and sarcasm, between revealing scandals, and playing with death, between the stinging satire, which draws a smile and puts a dagger in the heart, at the same time, it relies on presenting laughter with a special philosophy mixed with hysterical crying, which reveals and exposes failure, failure, downfall, and the decline of values in societies, and everything that is hidden.The research was divided into the first chapter, which included the methodological framework, and in it a presentation of the research problem, which is represented by the following question: (What is the way in which black comedy operates in television drama)? Then the researcher identified the terms in the search keywords.As for the second chapter, which is represented by (the theoretical framework), it was mentioned in three sections, the first topic: (black comedy, the historical introduction, and the concept), and the second topic: (representations of black comedy in television drama), while the third topic: (the work of the mediator’s language elements in employing black comedy with TV drama), and the research concluded a set of results and conclusions, including:1- The character is ranked first in the priority of employing her work because of its impact and dramatic effectiveness in breaking taboos and taboos with a satirical template in black comedy.2- Music and the rest of the elements of the audio stream are used through the melody that expresses a specific situation in contrast with the image in drawing the features of black comedy.